GKChP (Gosudarstvennyi komitet po chrezvychainomu polozheniiu) . GKChP (Gosudarstvennyi komitet po chrezvychainomu polozheniiu) . The State Committee on the State of Emergency . ГКЧП (Государственный комитет по чрезвычайному положению) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on the trial of members of the State Committee of the State of Emergency. Featured in the program: Nadein, Vladimir (Publicist); TSipko, Aleksandr Sergeevich (Political Scientist); Kosarev, Andrei Ivanovich (Historian) Обсуждения суда над Государственном комитетом по чрезвычайному положению (ГКЧП). В программе участвуют: Надеин, Владимир (Публицист); Ципко, Александр Сергеевич (Политолог); Косарев, Андрей Иванович (Историк)